2007
DOI: 10.1002/jnr.21309
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum‐associated degradation of the NR1 but not the NR2 subunits of the N‐methyl‐D‐aspartate receptor induced by inhibition of the N‐glycosylation in cortical neurons

Abstract: The N-methyl-D-aspartate receptor (NMDAR) is fundamental to normal and pathological functioning of neurons. The receptor subunits are N-glycosylated proteins synthesized in the endoplasmic reticulum (ER) that fold, mature, and oligomerize as they transit through the secretory pathway. Although the early processes of biogenesis are fundamental to NMDAR expression and function, our knowledge of them is nevertheless limited. Additionally, the investigation of NMDAR synthesis is highly relevant, in that ER dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The observed alterations may result from functional impairments of this enzymatic machinery; accordingly, previous studies showed that, in cortical neurons, the inhibition of the first enzymatic step of N -glycosylation enhances the degradation of nonglycosylated NR1, but not NR2A subunits (Gascón et al, 2007). The extensive N -glycosylation of NR1 (based on the attachment of high-mannose oligosaccharide side-chains onto 12 Asparagine sites) is essential for its oligomerization with NR2 subunits (Chazot et al, 1995; Standley and Baudry, 2000); thus, the increased expression in NR2A and NR2B may be paralleled by a reduced number of functional NR1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The observed alterations may result from functional impairments of this enzymatic machinery; accordingly, previous studies showed that, in cortical neurons, the inhibition of the first enzymatic step of N -glycosylation enhances the degradation of nonglycosylated NR1, but not NR2A subunits (Gascón et al, 2007). The extensive N -glycosylation of NR1 (based on the attachment of high-mannose oligosaccharide side-chains onto 12 Asparagine sites) is essential for its oligomerization with NR2 subunits (Chazot et al, 1995; Standley and Baudry, 2000); thus, the increased expression in NR2A and NR2B may be paralleled by a reduced number of functional NR1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the differences in amino acid sequence in the loops occur on or around predicted N-glycosylation sites, a mechanism used by chaperone proteins in the Golgi to identify and move proteins to distinct trafficking vesicles (Martinez-Maza et al, 2001; Nathanson, 2008). GluN2 subunits are glycosylated proteins (Clark et al, 1998) and glycosylation can affect the NMDA receptor’s assembly and function (Chazot et al, 1995; Everts et al, 1997; Standley and Baudry, 2000; Gascon et al, 2007). In polarized cells, a single glycosylation site can target proteins to the apical or basolateral membrane.…”
Section: Discussionmentioning
confidence: 99%
“…During assembly of heteromeric NMDA receptors, GluN1 subunits containing high-mannose glycans are ubiquitinated and degraded through the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway during changes in synaptic activity (Gascon et al 2007, Kato et al 2005). This process is regulated by a dendritic spine–localized F-box ubiquitin E3 subunit, SCF Fbx2 , that binds specifically to high-mannose glycans (Yoshida et al 2002).…”
Section: Ubiquitin-dependent Regulation Of Glutamate Receptors At Excmentioning
confidence: 99%